A systematic review of vulnerability analysis & penetration testing tools - Raja Sekhar, K; M, Pavanasurya; Bharti, Komal; G, Dhanya (International Journal of Engineering and Technology, 2017)
In Computer Security, the term vulnerability refers as a flaw in the system which creates a hole, giving an attacker a chance of taking control over the system. Any Software, Web application or anything related to computer product is vulnerable to attack in different ways like code stealing, sniffing of packets, hijacking the network, making the system compromised etc. In order to avoid such attacks a constant check has to be done and the check has to be done through various Pen testing tools. Penetration tools are one which is used to perform security check on an application to find the presence of exploitable vulnerabilities. In this paper, we look over the penetration tools like CODEPULSE (the code stealer), ETTERCAP (the Sniffer and Hijacker) and made a systematic review of various websites which are vulnerable to SQL Injection and Cross-site Scripting.Â Â
Keywords: Social Engineering; Penetration Testing; Exploit; SQL Injection; Cross Site Scripting; Glass Box Testing.